2020
DOI: 10.1161/circgen.120.003014
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Imaging of Aortic Valve Area From 34 287 UK Biobank Participants Reveals Novel Genetic Associations and Shared Genetic Comorbidity With Multiple Disease Phenotypes

Abstract: Background - The aortic valve is an important determinant of cardiovascular physiology and anatomic location of common human diseases. Methods - From a sample of 34,287 white British-ancestry participants, we estimated functional aortic valve area by planimetry from prospectively obtained cardiac MRI sequences of the aortic valve. Aortic valve area measurements were submitted to genome-wide association testing, followed by polygenic risk scoring and phe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The majority of brain structural MRI traits are highly heritable (heritability ranges from 0.6 to 0.8) 29 and the heritability of brain functional connectivity is largely between 0.2 and 0.6 30 . A few recent genome-wide association study (GWAS) have been separately conducted on CMR [31][32][33][34][35][36] and brain MRI traits [37][38][39][40][41][42] . Although MRI is widely used in clinical research and genetic mapping, few studies have used multiorgan MRI to examine heart-brain connections and identify the heart's and brain's shared genetic signatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of brain structural MRI traits are highly heritable (heritability ranges from 0.6 to 0.8) 29 and the heritability of brain functional connectivity is largely between 0.2 and 0.6 30 . A few recent genome-wide association study (GWAS) have been separately conducted on CMR [31][32][33][34][35][36] and brain MRI traits [37][38][39][40][41][42] . Although MRI is widely used in clinical research and genetic mapping, few studies have used multiorgan MRI to examine heart-brain connections and identify the heart's and brain's shared genetic signatures.…”
mentioning
confidence: 99%
“…To evaluate the genetic determinates underlying heart-brain connections, we performed GWAS for the 82 CMR traits to uncover the genetic architecture of heart and aorta. In comparison to existing GWAS of CMR traits [31][32][33][34][35][36] , our study used a much broader group of cardiac and aortic traits, which allowed us to identify the shared genetic components with a wide variety of brain-related complex traits and disorders. For example, Pirruccello, et al 35 mainly focused on 9 measures of the right heart, Aung, et al 31 analyzed 6 LV traits, and Thanaj, et al 36 studied 3 traits of diastolic function.…”
mentioning
confidence: 99%
“…The SNP rs11570508 associated with general CHD is located in a region that contains several genes linked to heart development, CHD and other cardiac phenotypes; MYL4, CDC27, GOSR2 and WNT9B (Goddard et al, 2017;Lahm et al, 2021;Orr et al, 2015;Sabour et al, 2018). A recent GWAS study on patients with anomalies of thoracic arteries and veins identified three significant SNPs within the GOSR2 locus in chromosome 17 close to rs11570508 (Lahm et al, 2021), and the chr17:45013271_T_C (rs17608766) variant in GOSR2 has been associated with a reduced aortic valve area (Córdova-Palomera et al, 2020) indicating importance of this locus in cardiac development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SNPs near GOSR2 have previously been implicated in variations in aortic valve area, aortic root diameter, and other cardiac dimensions. [24][25][26][27] Further, PALMD has been implicated as a susceptibility gene for calcific aortic stenosis. 24,28,29 This agreement lends credence to interesting novel loci, such as aortic root diameter's association with SNP rs80036911 on MECOM, a gene previously associated with left ventricular trabeculation.…”
Section: Discussionmentioning
confidence: 99%